Penyuluhan kesehatan seks pranikah pada siswi di MAN 3 Kota Makassar - Andi Khairul Musyawir; Momen Amalia (JOURNAL of Public Health Concerns, 2025)
Background: Adolescence is a transition period from childhood to adulthood, grouped in the age group of 11-24 years. In the adolescent phase, life is full of dynamics, marked by major changes in physical, emotional, and social psychological aspects. Premarital sex is a sensitive issue, especially related to its impact on reproductive health, psychology, and social life of adolescents. Comprehensive sex education and open communication can guide adolescents to make better decisions and live healthier lives. Purpose: To increase knowledge about the impact of premarital sex on students/adolescents. Method: This premarital sex counseling activity was carried out at MAN 3 Makassar with the topic of increasing knowledge about premarital sex among adolescents which was attended by 29 students as respondents, teachers and parties related to the public health community. The activity was carried out by presenting material (presentation), distributing leaflet media, discussions and interactive Q&A. Using pre-test and post-test questionnaires as a medium for measuring the level of knowledge of premarital sex in students. Results: Shows that 5 respondents have lower pre-test scores than post-test (Negative Ranks) with an average score of 6.50 out of a total score of 32.50. While 20 respondents have higher pre-test scores than post-test (Positive Ranks) with an average score of 14.63 out of a total score of 292.50. Furthermore, 4 respondents showed the same pre-test and post-test scores (Ties). These results indicate that the majority of respondents got an increase in scores from pre-test to post-test. Based on the Wilcoxon signed ranks test, the Z score was -3.551 with a p-value = 0.000. Conclusion: Counseling activities about premarital sex among students in high schools or equivalent can increase understanding, awareness and self-confidence in dealing with psychosocial problems, especially issues related to sexual norms. Increasing knowledge about premarital sex in students has a significant positive influence on thinking patterns to be more open and more responsible in making decisions related to sexual life. This counseling has proven effective in providing essential education for adolescents in developing healthier and more responsible views about premarital sex. Suggestion: With this community service activity, schools can integrate this information into the school curriculum and community activities to expand the reach and impact of education. Keywords: Counseling; Premarital sex; Students Pendahuluan: Remaja adalah masa transisi dari anak-anak menuju dewasa yang dikelompokkan usia 11-24 tahun. Pada fase masa remaja memiliki kehidupan yang penuh dinamika, ditandai dengan perubahan besar dalam aspek fisik, emosional, dan psikologi sosialnya. Seks pranikah menjadi isu yang sensitif, terutama terkait dampaknya pada kesehatan reproduksi, psikologi, dan kehidupan sosial remaja.  Pendidikan seks yang menyeluruh dan komunikasi yang terbuka dapat membimbing remaja untuk membuat keputusan yang lebih baik dan menjalani kehidupan yang lebih sehat. Tujuan: Untuk meningkatkan pengetahuan tentang dampak seks pranikah pada siswi/remaja. Metode: Kegiatan penyuluhan seks pranikah ini dilakukan di MAN 3 Kota Makassar dengan topik meningkatkan pengetahuan tentang seks pranikah di kalangan remaja yang dihadiri 29 siswi sebagai responden, para guru dan pihak terkait dengan komunitas kesehatan masyarakat. Kegiatan dilaksanakan dengan melakukan pemaparan materi (presentasi), membagikan media leaflet, diskusi dan tanya jawab inter aktif. Menggunakan kuesioner pre-test dan post-test sebagai media pengukuran tingkat pengetahuan seks pranikah pada siswi.   Hasil: Menunjukkan bahwa 5 responden memiliki nilai pre-test lebih rendah dibandingkan post-test (Negative Ranks) dengan nilai rata-rata 6.50 dari total nilai 32.50. Sedangkan 20 responden memiliki nilai pre-test lebih tinggi dibandingkan post-test (Positive Ranks) dengan nilai rata-rata 14.63 dari total nilai 292.50. Selanjutnya 4 responden menunjukkan nilai pre-test dan post-test yang sama (Ties). Hasil ini mengindikasikan bahwa mayoritas responden mendapatkan peningkatan nilai dari pre-test ke post-test. Berdasarkan uji wilcoxon signed ranks mendapatkan nilai Z sebesar -3.551 dengan p-value= 0.000. Simpulan: Kegiatan penyuluhan tentang seks pranikah di kalangan siswi di sekolah menengah atas atau sederajatnya dapat meningkatkan pemahaman, kesadaran dan kepercayaan diri dalam menghadapi permasalahan psikososial terutama isu-isu terkait norma seksualitas. Peningkatan pengetahuan tentang seks pranikah pada siswi memberikan pengaruh positif yang cukup signifikan terhadap pola pemikiran menjadi lebih terbuka dan lebih bertanggung jawab dalam membuat keputusan terkait kehidupan seksual. Penyuluhan ini terbukti efektif dalam memberikan edukasi yang esensial bagi remaja dalam mengembangkan pandangan yang lebih sehat dan bertanggung jawab mengenai seks pranikah. Saran: Dengan adanya kegiatan pengabdian kepada masyarakat ini sekolah dapat mengintegrasikan informasi ini dalam kurikulum sekolah dan kegiatan komunitas untuk memperluas jangkauan dan dampak edukasi.